TASK-BASED LANGUAGE TEACHING IN DEVELOPING COMMUNICATIVE COMPETENCE OF ESP LEARNERS - Kurbaniyazova, Sarbinaz Ametovna (SCIENCE and SOCIETY, 2026)
The paper explores the effectiveness of Task-Based Language Teaching (TBLT) in developing communicative competence among ESP learners, particularly History students at the B1–B2 level. The findings show that TBLT improves students’ fluency, interaction, and ability to use language in academic contexts. The results suggest that TBLT is an effective approach for enhancing both language skills and subject-related communication in ESP instruction.